A Simulation Study of Surface Plasmons in Metallic Nanoparticles: Dependence on the Properties of an Embedding a‐Si:H Matrix. Issue 3 (6th December 2017) - Fantoni, Alessandro; Fernandes, Miguel; Vygranenko, Yuri; Louro, Paula; Vieira, Manuela; Alegria, Elisabete C. B. A.; Ribeiro, Ana; Texeira, Daniela
Abstract : The development and realization of a plasmonic structure based on the LSP interaction of metal nanoparticles with an embedding matrix of amorphous silicon is proposed. As a planned application, this structure will need to be usable as the basis for a sensor device applied in biomedical applications, after proper functionalization with selective antibodies. The final sensor structure needs to be low‐cost, compact, and disposable. The study reported in this paper aims to analyze varied materials for nanoparticles embedded in an amorphous silico matrix. Metals of interest for nanoparticles composition are aluminum and gold. As a comparison term, a non‐plasmonic material like alumina, resulting from oxidation of Al nanoparticles, is also considered. As a preliminary approach to this device, we study in this work the optical properties of spherical metal nanoparticles embedded in an amorphous silicon matrix, as a function of size and metal type. Following an analysis based on the exact solution of the Mie theory, experimental measurements realized with arrays of metal nanoparticles are compared with the simulations. Abstract : The development and realization of a plasmonic structure based on the LSP interaction of metal nanoparticles with an embedding matrix of amorphous silicon to be used in biomedical applications is proposed. Metals of interest are aluminium and gold. Optical properties of metal nanospheres embedded in an amorphous silicon matrix, are studied as a function of size and metal type.